Kontribusi Impulsive Buying terhadap Post Purchase Regret Produk Skincare di TikTok Shop pada Mahasiswi Kota Padang - Chantika, Liyoni Aprilia Dwi; Dwatra, Free Dirga (Lembaga Yasin AlSys, 2025)
The purpose of this study is to determine the contribution of impulsive buying to post-purchase regret of skincare products at TikTok Shop for female students in Padang City. The phenomenon of increasing impulsive shopping behavior on the TikTok Shop platform, especially for beauty products, is often followed by feelings of regret after purchase. This study uses quantitative methods with a correlational approach. The sample consisted of 100 female college students in Padang city who were taken using purposive sampling technique. Findings from simple linear regression analysis indicated a significant positive contribution between impulsive buying and post-purchase regret, with a significance value of 0.000 (p < 0.05), also obtained an R square value of 0.757. This shows that impulsive buying contributes 75.7% to post-purchase regret. Therefore, if the higher the level of impulsive buying, the higher the likelihood of individuals experiencing post-purchase regret.